1999
DOI: 10.1177/03635465990270021301
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Anterior and Posterior Cruciate Ligaments After Knee Dislocation

Abstract: We reviewed the results in 13 patients who underwent simultaneous allograft reconstruction of both the anterior and posterior cruciate ligaments after a knee dislocation (nine acute and four chronic injuries). Seven patients sustained related medial collateral ligament injuries and six patients had posterolateral complex injuries. Ligament reconstructions were performed using fresh-frozen Achilles or patellar tendon allografts. At follow-up evaluation (mean of 38 months), only one patient described the reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
119
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(134 citation statements)
references
References 23 publications
12
119
2
1
Order By: Relevance
“…It is now established that for patients sustaining Grade III isolated PCL injuries and for patients sustaining high-grade PCL injuries associated with a multiligamentous knee injury, surgical intervention may lead to improved subjective outcomes, decreased side-to-side differences in stability, and decreased laxity on stress radiographs as compared with nonoperative treatment with appropriate patient selection [5,11,13,23,25,36,39,47,54]. The ideal timing of surgical treatment and the ideal surgical technique for isolated Grade III PCL injuries and PCL injuries associated with multiligamentous knee injuries remain controversial [24,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now established that for patients sustaining Grade III isolated PCL injuries and for patients sustaining high-grade PCL injuries associated with a multiligamentous knee injury, surgical intervention may lead to improved subjective outcomes, decreased side-to-side differences in stability, and decreased laxity on stress radiographs as compared with nonoperative treatment with appropriate patient selection [5,11,13,23,25,36,39,47,54]. The ideal timing of surgical treatment and the ideal surgical technique for isolated Grade III PCL injuries and PCL injuries associated with multiligamentous knee injuries remain controversial [24,35].…”
Section: Discussionmentioning
confidence: 99%
“…It is now generally accepted that patients with isolated PCL injuries with greater than 10 mm of posterior laxity or high-grade PCL injuries associated with multiligamentous knee injuries have improved subjective outcomes, side-to-side differences in stability, and decreased laxity on stress radiographs with operative intervention [5,11,13,23,25,36,39,45,47,54]. This may be the result of restoration of normal knee kinematics and a decreased propensity to develop medial compartment and patellofemoral compartment arthrosis [7,19,26,28,46,51].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for treating knee dislocations have been varied and controversial [18,19,40]. Several authors have reported [9,13,41] a loss of flexion of less than 12°, improved stability, and high subjective scores with single-stage surgery of all involved stabilizing structures.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for the management of knee dislocation are varied and controversial [18,19,40]. Nonoperative treatment generally results in stiff knees with limited ROM and low functional scores [1,16,27,37].…”
Section: Introductionmentioning
confidence: 99%
“…Patellar tendon, quadriceps tendon and hamstring tendons of the ipsi- or contralateral side have been used as autografts for reconstruction in traumatic knee dislocations. Several authors prefer allografts (Achilles tendon, patellar tendon, tibialis anterior tendon, hamstring tendons) as surgical time and donor site morbidity may be decreased in this complex reconstructive setting[19,23,32]. To our knowledge there is no study demonstrating the superiority of allografts in terms of clinical outcome and ligament laxity in comparison to autografts in multi-ligament injured knees.…”
Section: Discussionmentioning
confidence: 99%